Adult education - self exploration for women - Newman, Joel; McLachlan, Mary Jane (Canadian Journal of Counselling and Psychotherapy, 2012)
As schools expand career counselling services to include the adult community, the special needs of women in mid-life require new approaches. Such a programme involving communication skills, assertion training, outside speakers, vocational testing, life style planning and goal setting is outlined in this paper.